Navigating the VUCA Terrain: Unveiling HR Strategies for Modern Organizational Agility - Chowdhury, Manali (SEISENSE Journal of Management, 2024)
Purpose- This study explores the consequences of HRM in the contemporary VUCA environment, with a particular emphasis on leadership styles, learning, incentives, and recruiting. It aims to understand leadership ideologies and efficient management techniques. Design/Methodology- The study employs a qualitative methodology that incorporates content analysis, historical research, and theoretical development. In the VUCA era, several data sources are methodically selected to improve organizational performance. Findings- It sheds light on leadership theories and efficient HR procedures, providing guidance for modifying hiring procedures, creating a culture of learning, and creating fulfilling initiatives. The benefits of Digital HR Architecture are highlighted, with examples from companies like IBM, Google, and Salesforce. Practical Implications- The research underscores the significance of considering cultural inclusion and workforce diversity for sustainable growth. Originality- Advancing our understanding of HR procedures in a tech-driven VUCA environment, this study offers practical insights based on real-world case studies and evidence-based research, guiding organizations towards sustainable development.